Aplikasi kleinano dari tuf volkan Gunung Salak Indonesia sebagai adsorben alami kontaminan anionik: Fosfat perairan - Sudadi, Untung; Anggriawan, Rendy; Anwar, Syaiful (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
Indonesia is rich with volcanic tuff-derived Andisols that contain variable charged minerals. This research was aimed at to extract nanoclays (diameter <200 nm) from volcanic tuffs, and to evaluate their potential as natural adsorbent of phosphate as contaminant in waters. Volcanic tuffs were taken from the 3rd (tv3) and 4th(tv4) layers of an Andisol profile at the foot slope of Salak Mountain Indonesia using dispersion-ultrasonication-centrifugation-dialysis separation procedure. By dispersing the materials in an acid condition (pH 4.0) followed with ultrasonication, it could be separated positively-charged nanoclays (nc3 and nc4) from the negative ones. The separated nanoclays were then purified using centrifugation and membrane dialysis techniques. Potential of the extracted nanoclays as natural phosphate adsorbent was evaluated by characterizing their adsorption maxima (b values) according to the Langmuir isothermal adsorption model. It could be extracted 2.82 mg nc3/g tv3 and 4.29 mg nc4/g tv4. The b values of nc3 at 12, 24, and 48 hours equilibration time (76.48, 92.10, and 117.54 mg P/g nc3) were higher than those of nc4 (50.17, 59.52, and 71.99 mg P/g nc4). The most effective equilibration-time was 48 hours. The extracted nanoclays were considered prospective as natural adsorbent for removal phosphate contaminant in waters